La rigenerazione delle aree interne:: è possibile una nuova dimensione rurale? - Verderosa, Benedetta (OS. Opificio della Storia, 2021)
Valorisation and revitalization theories, related to inland areas, recently have combined with the ecological culture, especially as regards topics such as the repossession of local dimension, small villages lifestyle and the return of investment in agriculture. Despite the agriculture has been for years the main economic activity of inland areas, the contemporary agricultural production requires the introduction of an advanced model: multifunctional agriculture. It’s not a simple economic practice but it includes several services: it’s a social practice, inspired by an advanced connection with nature that introduce a new lifestyle. Multifunctional agriculture produces not only commodities, but essential services for the territory, such as the soil protection from erosion processes, the preservation of biodiversity, the defence and enhancement of the rural landscape, air and water quality, eco-friendly tourism and new practices of sociability.